1991
DOI: 10.1136/gut.32.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Cell recovery during segmental intestinal perfusion in healthy subjects and patients with Crohn's disease.

Abstract: The recovery of cells arising from small intestinal mucosa alone was studied during continuous perfusion of a closed segment of jejunum. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Elevated hyaluronan levels are associated with inflammatory processes including inflammatory bowel disease (1). Therefore, the ability of several proinflammatory mediators to modulate hyaluronan expression in jejunum-derived mesenchymal cells was examined.…”
Section: Effects Of Proinflammatory Mediators On Hyaluronan Accumulatmentioning
confidence: 99%
“…Elevated hyaluronan levels are associated with inflammatory processes including inflammatory bowel disease (1). Therefore, the ability of several proinflammatory mediators to modulate hyaluronan expression in jejunum-derived mesenchymal cells was examined.…”
Section: Effects Of Proinflammatory Mediators On Hyaluronan Accumulatmentioning
confidence: 99%
“…12 Catheters with 2 inflatable balloons for isolation of intestinal segments in humans were, to our knowledge, described for the first time in 1936. 13 Ahrenstedt et al 14 showed that epithelial cells could be collected by means of aspiration from isolated segments. Since then, this technique of segmental jejunal perfusion has been adapted for measurements of secretion of endogenous substances into the small intestine 15 and for assessment of drug absorption from the human small intestine.…”
mentioning
confidence: 99%
“…A good correlation exists between the measured jejunal P eff 2 and the fraction dose absorbed of drugs in humans determined by pharmacokinetic studies. Using this technique, the majority of shed human enterocytes collected from an intestinal perfusion were still functionally active and did not show signs of apoptosis (Ahrenstedt et al, 1991;Glaeser et al, 2002). Therefore we not only investigated the transport and metabolism of phytochemicals in the human jejunum but also their effect on the short term changes in mRNA expression of phase II enzymes in shed enterocytes after perfusion.…”
mentioning
confidence: 99%